Comparative biokinetics of pristine and sulfidized Ag nanoparticles in two arthropod species exposed to different field soils. Issue 9 (13th August 2020) - Talaber, Iva; Van Gestel, Cornelis A. M.; Jemec Kokalj, Anita; Marolt, Gregor; Novak, Sara; Zidar, Primož; Drobne, Damjana
Abstract : Ag bioaccumulation upon exposure to pristine Ag NPs is of bigger concern in acidic sandy soils, but not in case of the environmentally relevant sulfidized Ag NPs, which do not bioaccumulate in P. scaber or F. candida . Abstract : Silver nanoparticles (Ag NPs), incidentally or intentionally released to soil ecosystems, have the potential to accumulate in organisms. Due to the great variety of natural (field) soil and its interactions with Ag NPs, the few available biokinetic studies performed on standard soils are not sufficient for an environmentally relevant assessment of Ag NP bioaccumulation. In this study, we analyzed the biokinetics of pristine and sulfidized Ag NPs (Ag2 S NPs) in two arthropod species with different routes of exposure to soil contaminants (isopod Porcellio scaber and springtail Folsomia candida ) exposed to 4 different soils, widely differing in chemical and physical properties. Using the biokinetic constant of uptake as proxy for bioavailability, we found soil pH and soil texture to be the strongest predictors of Ag bioavailability to isopods and springtails, respectively. Both organisms accumulated Ag when exposed to pristine Ag NPs, which suggests a risk for food-chain accumulation of Ag. In contrast, no Ag bioaccumulation was detected in the case of the poorly soluble Ag2 S NPs, which is the more environmentally relevant form of Ag NPs. Our study corroborates the dominant role of dissolution in Ag NP bioavailability and draws attention to the biological differences between different soil dwelling organisms modulating their Ag NP exposure.